The Forgotten Moralist: Friedrich Schleiermacher and the Science of Spirit - Sockness, Brent W. 1962- (2003)
For some two hundred years now, Friedrich Daniel Ernst Schleiermacher (1768–1834) has been the subject of intense interest and heated debate among Christian theologians. As the author of a seminal work in the theory of religionFriedrich Schleiermacher, On Religion: Speeches to its Cultured Despisers (trans. Richard Crouter; Cambridge: Cambridge University Press, 1988). as well as a treatise in Christian doctrine that ranks second to none for its originality, methodological self-consciousness, and systematic stringency,Friedrich Schleiermacher, The Christian Faith (trans. H. R. MacIntosh and J. S. Stewart; Edinburgh: T&T Clark, 1928). In 1839 Johannes von Kuhn of the Catholic Tübingen school rightly observed that “among all the theologians of later and contemporary times, only Schleiermacher can be compared to [Thomas Aquinas] so far as scientific force and power are concerned.” Cited in Robert Stalder, Grundlinien der Theologie Schleiermachers: I. Zur Fundamentaltheologie (Veröffentlichungen des Instituts für europäische Geschichte Mainz 53; Wiesbaden: F. Steiner, 1969) ix. Schleiermacher's significance in the history of modern theology is secure. By his liberal Protestant sympathizers he has been hailed as the “Reformer of theology,” the pioneer of a style of theologizing that is as peculiarly suited to the distinctively Protestant understanding of faith as it is capable of meeting the intellectual demands of the modern world.This honorific title was widespread in the second half of the nineteenth century and prior to the rise of dialectical theology in the twentieth. Representative is Wilhelm Herrmann, “Die Lage und Aufgabe der evangelischen Dogmatik in der Gegenwart” (1907), in ibid., Schriften zur Grundlegung der Theologie (ed. Peter Fischer-Appelt; 2 vols.; Munich: Kaiser Verlag, 1966–1967) 2:16–20. To his equally numerous and vocal theological critics, Schleiermacher represents the enslavement of the Word of God to a pagan mysticism and speculative philosophy,Emil Brunner, Die Mystik und das Wort: Der Gegensatz zwischen moderner Religionsauffassung und christlichem Glauben dargestellt an der Theologie Schleiermachers (Tübingen: J. C. B. Mohr, 1924). the subjectivistic collapse of Christian theology into anthropology,Karl Barth, introduction to Ludwig Feuerbach, The Essence of Christianity (New York: Harper, 1957). or, more recently, the classic exemplar of a linguistically naïve and apologetically motivated “experientialist-expressivist” misunderstanding of the nature of religious doctrine.George A. Lindbeck, The Nature of Doctrine: Religion and Theology in a Postliberal Age (Philadelphia: Westminster Press, 1984). To friend and foe alike, however, he remains—for better or worse—the undisputed “father of modern theology.”In the English-speaking world, the work of B. A. Gerrish remains the best introduction to, and most sophisticated treatment of, Schleiermacher's theological achievement. See B. A. Gerrish, A Prince of the Church: Schleiermacher and the Beginnings of Modern Theology (Philadelphia: Fortress Press, 1984) and the essays devoted to Schleiermacher in Continuing the Reformation: Essays on Modern Religious Thought (Chicago: University of Chicago Press, 1993), The Old Protestantism and the New: Essays on the Reformation Heritage (Chicago: University of Chicago Press, 1982), and Tradition and the Modern World: Reformed Theology in the Nineteenth Century (Chicago: University of Chicago Press, 1978).